Grain-size characteristics of deposits derived from different glacigenic environments of the Schirmacher Oasis, East Antarctica - Srivastava, Ashok K.; Ingle, Pravin S.; Lunge, Harihar S.; Khare, Neloy (Geologos, 2012)
Sediment samples have been collected from the Schirmacher Oasis and adjoining area in East Antarctica; these areas consist of polar ice, ice-free area, lakes and the coastal shelf area. The 37 samples have been analysed for their grain-size parameters and statistical relationships. The oasis is characterised by ongoing glacial processes, including deposition and erosion of the sediments by ice, meltwater and winds, thus influencing the sediments in various ways. Basic statistical grain-size parameters like graphic mean, standard deviation, skewness and kurtosis have been calculated for the four units. The sediments of all areas are almost all poorly to very poorly sorted, fine-skewed to near-symmetrical and platykurtic to leptokurtic in nature. Bivariate plots between the grain-size parameters have been interpreted. They do, apart from a few exceptions, not show any trend suggesting relationships between the sediments of the four landscape types. Both t- and F-tests have been applied on the samples, and the phi values and grain-size parameters have been analysed; these show that the group variances of the samples are not significant, but that the phi-values are significant.